2013
DOI: 10.3389/fnagi.2013.00020
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Working Memory Training Scheme in Older Adults

Abstract: Working memory is a cognitive process that is particularly vulnerable to decline with age. The current study sought to evaluate the efficacy of a working memory training scheme in improving memory in a group of older adults. A 5-week online training scheme was designed to provide training in the main components of Baddeley’s (2000) working memory model, namely auditory and visuospatial short-term and working memory. A group of older adults aged between 64 and 79 were randomly assigned to a trainee (n = 19) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…Five clinical studies were randomized controlled clinical trials (McAvinue et al, 2013; Corbett et al, 2015; Rose et al, 2015; Walton et al, 2015; Hyer et al, 2016), and one study included two randomly allotted intervention groups (Bozoki et al, 2013). All of them applied only computerized cognitive training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five clinical studies were randomized controlled clinical trials (McAvinue et al, 2013; Corbett et al, 2015; Rose et al, 2015; Walton et al, 2015; Hyer et al, 2016), and one study included two randomly allotted intervention groups (Bozoki et al, 2013). All of them applied only computerized cognitive training.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the studies in Table 1 indicate that computerized cognitive training can lead to the improvement of cognitive functions such as reasoning skills (Corbett et al, 2015), short-term memory (McAvinue et al, 2013), working memory (Hyer et al, 2016), processing speed and visual working memory (Walton et al, 2015) in particular. However, this training should be performed over a longer time span since a short-term cognitive training mainly has an impact on short-term memory with temporary effects (McAvinue et al, 2013; Walton et al, 2015).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two recent intervention studies (McAvinue et al, 2013;Sandberg et al, 2014) failed to show evidence of improvement in WM capacity. A 5-week online randomized adaptive training study based on the Baddeley model (Baddeley, 2000) to train auditory and visual-spatial short-term WM (McAvinue et al, 2013) showed improvement in short-term memory but not in WM despite the extensive training on updating and n-back tasks. The expansion of auditory short-term memory up to 6 months, and the transfer to long-term episodic memory (although not maintained at follow-up) is interesting.…”
Section: Computerized Brain Training In Agingmentioning
confidence: 95%
“…This study used an online CT programme that specifically targets working memory and was developed by our group (Dillon et al., ; Donohoe et al., ; Hargreaves et al., ; McAvinue et al., ). The programme consisted of education on working memory, strategy‐based learning and practice of nine working memory training exercises.…”
Section: Methodsmentioning
confidence: 99%